2019
DOI: 10.1002/navi.324
|View full text |Cite
|
Sign up to set email alerts
|

Disciplined oscillators for traceable frequency and time in metrology and financial sectors

Abstract: Laboratory sources for standard frequency and time that receive external time signals to control their built-in oscillators are widely used wherever accurate and stable frequency and time, optionally with universal synchronization, are required. We propose a method to obtain traceability of such signals to Coordinated Universal Time (UTC) and particularly to UTC(PTB), its realization by the Physikalisch-Technische Bundesanstalt (PTB). The role of PTB's weekly published Time Service Bulletin is discussed in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…10 d of data were used. In figure 10 the frequency instability in dependence of the averaging time is depicted (data were previously shown in [23,32]). Due to the steering process a local maximum at τ ≈ 1000 s exists.…”
Section: Operation Of a Domentioning
confidence: 85%
See 2 more Smart Citations
“…10 d of data were used. In figure 10 the frequency instability in dependence of the averaging time is depicted (data were previously shown in [23,32]). Due to the steering process a local maximum at τ ≈ 1000 s exists.…”
Section: Operation Of a Domentioning
confidence: 85%
“…Significant documentation on traceability to US standards was published earlier [21,22]. Those form together with previous papers of this work's authors [23][24][25] the foundation of this report. Based on already available guidelines [26,27] we illustrate in the next section a full scheme for traceable frequency measurements with counters in a calibration laboratory.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Other UTC services have begun to be offered, using technologies such as time synchronization over commercial telecommunication networks, custom dark fibre and GNSS [14][15][16] and emphasize different performance characteristics: cost, synchronization uncertainty, holdover times and alert features. Many of these services can be considered as remote disciplined oscillators using rubidium or quartz frequency standards as local oscillators.…”
Section: Traceable Utc Servicesmentioning
confidence: 99%
“…In its disciplined mode, the RC s unit's time and frequency are disciplined by the RC algorithm using ongoing commonview time transfers between the client's RC s and the RC p unit at NRC. To estimate the uncertainty, we consider uncertainty components largely following Lombardi [11] and Piester et al [16], as shown in table 1. We evaluate the disciplined stability using the standard deviation of repeated measurements of the RC in its servo loop at NRC for nearly-zero baseline (figure 2), and attribute the slowest variations to changes in the mean hardware calibration.…”
Section: Time Offset Uncertainty-disciplined Modementioning
confidence: 99%